Augmented Reality Techniques in Industrial Warehouse Logistics in Mining Industry; IOP Conference Series: Earth and Environmental Science; Vol. 688 : Ecology and safety in the technosphere: current problems and solutions - Rodnichenko E. K. Evgeny Konstantinovich; Gorlenkov D. V. Denis Viktorovich; Petrov P. A. Pavel Andreevich; Timofeev V. Yu. Vadim Yurievich (2021, 2021)
Title screen